Axio-Awareness Principle in Javanese Marriage Prohibition as a Normative Framework for Anticipating Divorce Risk - Ramadhita Ramadhita; Sudirman Sudirman; Miftahul Huda (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to examine the principle of axio-awareness embedded in Javanese marriage prohibitions as a locally grounded normative framework for anticipating divorce risks. While existing studies on Javanese marital customs largely emphasise anthropological or theological dimensions, their normative rationality as a form of preventive jurisprudence in contemporary family law discourse remains underexplored. This research is motivated by the increasing rate of early-stage divorce, particularly within the first five years of marriage, indicating structural and psychological unpreparedness among couples in navigating the initial phases of family life. Employing a non-doctrinal qualitative approach, this study analyses Javanese marriage prohibitions as manifestations of the values of eling lan waspada (moral awareness and vigilance), situating them within an impact-awareness reasoning framework. Rather than asserting empirical causality, the analysis constructs these prohibitions as socio-cultural mechanisms that foster anticipatory reflection, moral prudence, psychological readiness, and the reinforcement of parental and senior authority in marital decision-making processes. The findings reveal that such prohibitions function as culturally embedded preventive norms aligned with key principles in Islamic jurisprudence, particularly iḥtiyāṭ (legal precaution) and sadd al-dharā’iʿ (blocking the means to harm), both of which emphasise the prevention of potential harm (mafsadah) and the promotion of family welfare (maṣlaḥah). This study contributes to the discourse by reframing Javanese marriage prohibitions not merely as traditional beliefs but as a form of culturally rooted normative prudentialism that enhances risk awareness in family formation and offers a relevant preventive paradigm for contemporary family law.